Analysis of the characteristics of throwing techniques in martial arts - Levitskiy, A.G.; Matveev, D.A.; Mikhaylovskiy, S.P.; Gromov, M.M. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to identify the biomechanical characteristics of technical and tactical movements based on an analysis of the trajectories of the centres of gravity of various segments of the athlete’s body. Methods and structure of the study. During a match, the athlete performs movements, including those influenced by a force field. To characterise the field, a model comprising 14 segments of the human body was used. Using artificial intelligence, programmes have been developed that enable the calculation of the trajectories of the centres of gravity of the body segments and the saving of the resulting data to separate files. Results and conclusions. Based on the trajectories of the centres of gravity of the body segments, the nature of the force field at various points in space was determined. Analysis of these trajectories has provided objective insights into the execution of technical and tactical movements by highly skilled athletes, enabling the exploration of new approaches to designing the training process. The use of the proposed analysis in the training process will improve the performance of students in competitive activities and increase their motivation to continue practising martial arts.